THE EFFECTS OF SECONDARY SCHOOL STUDENTS TRUANT BEHAVIOUR ON EDUCATIONAL DEVELOPMENT: COUNSELING INTERVENTION - Abdullahi, Mustapha Ibrahim (Sokoto Educational Review, 2020)
This paper examined secondary school students’ truant behaviour on Educational development. It looked at the causes of truancy from the perspective of child factors, home, school, pee r groups and socio economic factors. It succinctly explained the counseling intervention that can be employed to salvage the situation.